2009
DOI: 10.1094/pdis-93-2-0180
|View full text |Cite
|
Sign up to set email alerts
|

New Host Races of Meloidogyne arenaria, M. incognita, and M. javanica from Horticultural Regions of Spain

Abstract: In total, 140 populations of the genus Meloidogyne collected from representative horticultural regions of Spain and maintained at the Department of Agroecology, Institute of Agrarian Sciences, Madrid were characterized using perineal morphology, sequenced characterized amplified region polymerase chain reaction with species-specific primers, and bioassay. Using a modified North Carolina differential host test as a basis, 13 Meloidogyne populations did not fit into the published race scheme. These populations h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 9 publications
2
14
1
4
Order By: Relevance
“…In the present work, all the RKN isolates infested the susceptible cultivar DLL, and were considered pathogens of pepper. This contrasts with results from the previous study (Robertson et al, 2009), which showed that the M-jav isolate, belonging to race 1, was non-pathogenic on pepper. This discrepancy is probably because, in that investigation, Sonar, rather than DLL, was used as the susceptible pepper variety in (Hendy et al, 1985).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present work, all the RKN isolates infested the susceptible cultivar DLL, and were considered pathogens of pepper. This contrasts with results from the previous study (Robertson et al, 2009), which showed that the M-jav isolate, belonging to race 1, was non-pathogenic on pepper. This discrepancy is probably because, in that investigation, Sonar, rather than DLL, was used as the susceptible pepper variety in (Hendy et al, 1985).…”
Section: Discussioncontrasting
confidence: 99%
“…The three M. incognita isolates were from three greenhouses in Murcia (Spain). All isolates were identified at the reference laboratory of the Consejo Superior de Investigaciones Cient ıficas (CSIC, Madrid) where it was determined that the M. arenaria isolate belonged to race 3, M. javanica isolate belonged to race 1 and M. incognita isolates belonged to race 2, based on the North Carolina differential host test (Robertson et al, 2006(Robertson et al, , 2009L opez-P erez et al, 2011). M-are, M-jav and Mi-avir isolates were maintained and multiplied on the susceptible tomato cultivar Marmande Claudia (Clausse Tezier) and Mi-virCH and Mi-virB isolates on Me3 pepper Atlante (Ramiro Arnedo).…”
Section: Nematode Isolatesmentioning
confidence: 99%
“…A imunidade apresentada pelas plantas de pimentas e pimentões observada neste estudo corrobora com os resultados obtidos por Peixoto et al (1995) Sabe-se que a existência de raças entre as espécies do gênero Meloidogyne dificulta o manejo das áreas infestadas por esses agentes. Entretanto, para M. javanica os estudos de raças (Rammah & Hirschmann, 1990;Carneiro et al, 2003;Robertson & Díez-Rojo, 2009) sugerem que a mais comumente encontrada no Brasil seria a raça 1 ou 5, uma vez que o parasitismo em pimentão (raça 2 e 4) ou em amendoim (raça 3 e 4) foram relatados sobretudo em espécies encontradas no continente africano e na Índia. Estudos no Brasil sobre determinação de raças de M. javanica ainda são escassos, principalmente, pela baixa frequência com que estas foram constatadas (Carneiro et al, 2003) e também pela ocorrência de populações atípicas (Stanton & O´Donell, 1998 De acordo com os resultados obtidos por Inomoto et al (2006), as espécies vegetais guandu 'Fava Larga' e mucuna cinza apresentaram-se suscetíveis a M. javanica, sendo que mucuna preta, C. spectabilis, C. breviflora e guandu anão apresentaram-se como resistentes, corroborando com os resultados verificados neste estudo.…”
Section: Discussionunclassified
“…O gênero Meloidogyne constitue o grupo de nematoides fitoparasitos mais importante para as olerícolas, devido à sua ampla distribuição em todo país, polifagia e à diferença biológica ligada ao parasitismo entre populações da mesma espécie (Pimenta & Carneiro, 2005). A determinação de algumas dessas raças já vem sendo bastante estudadas e difundidas, como no caso das raças expressas pela espécie M. incognita; entretanto, no caso de M. javanica, apesar de estudos que demonstram a determinação de raças (Rammah & Hirschmann, 1990;Carneiro et al, 2003;Robertson & Díez-Rojo, 2009), essa classificação ainda causa alguma controvérsia. Assim sendo, tais fatores vêm dificultando a implementação de programas de resistência varietal e rotação de culturas, que são as medidas de controle de Meloidogyne mais eficientes e viáveis em nossas condições (Pimenta & Carneiro, 2005).…”
Section: Introductionunclassified
“…Türkiye'de biber kültürlerinde dayanıklılık ıslahında kullanılan hatlar ile M. javanica popülasyonlarının patojenitesi ile ilgili çok kapsamlı bir çalışma bulunmamaktadır. Ayrıca Meloidogyne türlerinde yeni ırkların değerlendirilmesinde dayanıklı domates ve biber hatlarından yararlanılabileceği rapor edilmiştir [7].…”
Section: Introductionunclassified